Revolutionizing OBE with CO-AIMS - Mat Saat, Ezril Hisham; Othman, Norhalida; Muhamad, Nur Amalina; Abdul Rahman, Noor Hasliza; Wan Zazrajmir Halim, Wan Muhammad Alif Daniel (2025)
The advancement of Outcome-Based Education (OBE) in higher education calls for dynamic and sustainable systems that can effectively assess, monitor, and enhance student performance and lifelong learning outcomes. In response to this educational imperative, the College of Engineering Academic Information Management System (CO-AIMS) was developed by the Faculty of Electrical Engineering, UiTM Johor branch, Pasir Gudang campus to provide a comprehensive digital platform aligned with the goals of sustainable and innovative education. CO-AIMS integrates advanced computing technologies and utilizes the Rapid Application Development (RAD) model to address limitations in traditional tracking methods, such as fragmented data, manual reporting, and lack of real-time analytics. The system empowers academic advisors and curriculum managers to assess Program Outcome (PO) achievements at individual, course, and cohort levels through interactive dashboards, automated reports, and trend analytics. This data-driven approach not only promotes Continuous Quality Improvement (CQI) in curriculum delivery but also enhances institutional decision-making and transparency. Uniquely designed for scalability and adaptability, CO-AIMS ensures secure, cloud based access and role-specific functions for stakeholders, supporting its implementation across faculties and campuses. Its innovation lies in transforming static assessment practices into a responsive, tech-enabled ecosystem that fosters sustainable education through empowerment, inclusivity, and lifelong learning principles. CO-AIMS is directly transforming education and advancing innovation by bridging critical gaps in academic data management and enabling a future ready academic environment that supports both educators and learners. This initiative shows how technology can be effectively leveraged to create resilient and intelligent academic ecosystems for an empowered world.